Pengolahan Hasil Non-Test Angket, Observasi, Wawancara Dan Dokumenter - Rima damayanti; Nuril Huda; Dina Hermina (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Education cannot be separated from evaluation because evaluation is one of the most important basic components in education which must be carried out in a planned and systematic manner, of course, to know and determine student learning outcomes. Evaluation is divided into two categories, namely test and non-test. The test form of evaluation is often used by teachers, but non-test evaluation is not much sought after by teachers because the instrument is quite complicated. Therefore, the aim of this research is to find out how non-test evaluation is used and its obstacles to learning. The approach used in the qualitative approach is the description method and data collection techniques through interviews. From the data we got, the school uses non-test evaluation techniques as stated in the assessment in the 2013 curriculum in accordance with the learning objectives. Apart from that, there are obstacles experienced by teachers in using non-test evaluation, such as teachers' lack of skill in preparing non-test instruments, students who do not understand the implementation of non-test evaluation, lack of time in making non-test instruments. To overcome existing obstacles, teachers must improve their skills in making non-test instruments, teachers must choose what form of test they want to use, and teachers must prepare evaluation instruments before carrying out learning.